2017
DOI: 10.1007/s10597-017-0205-9
|View full text |Cite|
|
Sign up to set email alerts
|

Mental Health Needs and Psychoactive Drug Use in a User Population of the Family Health Strategy (FHS) in Ribeirão Preto, São Paulo, Brazil

Abstract: This cross-sectional study was conducted in Family Health Care's field of  Ribeirão Preto city, São Paulo, Brazil to identify the prevalence of substance-related disorders and mental distress among patients with mental disorders. We also aimed to identify sociodemographic and social support risk factors. The data collection was done using medical records, the Social Support Questionnaire (SSQ-6), Self Report Questionnaire (SRQ-20) and home visits. Of the 272 families studied, 211 contained individuals with men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
0
0
1
Order By: Relevance
“…In this sense, the data obtained may indicate that some cases, due to their complexity and severity, require recurrent hospital care in addition to the usual monitoring of the Family Health Strategy. 12 In a survey carried out in the Minas Gerais State, hospital admissions due to disorders caused by substance abuse were identified, of which, as observed in the present study, there were episodes of readmission. In New York city, a study revealed a predominance of hospitalizations for depressive episodes for those patients with a history of abuse of psychoactive substances.…”
Section: Discussionsupporting
confidence: 61%
“…In this sense, the data obtained may indicate that some cases, due to their complexity and severity, require recurrent hospital care in addition to the usual monitoring of the Family Health Strategy. 12 In a survey carried out in the Minas Gerais State, hospital admissions due to disorders caused by substance abuse were identified, of which, as observed in the present study, there were episodes of readmission. In New York city, a study revealed a predominance of hospitalizations for depressive episodes for those patients with a history of abuse of psychoactive substances.…”
Section: Discussionsupporting
confidence: 61%
“…Foi observado que fluoxetina, sertralina, diazepam e fenobarbital foram os medicamentos com o maior consumo no município estudado, considerando o consumo total, medido pela DDD/1.000PD e DDD75%/1.000PD, no ano de 2012. Luis et al 15 verificaram que mais da metade dos pacientes com doenças mentais atendidos em unidades da Estratégia Saúde da Família (ESF) da região oeste de Ribeirão Preto apresentaram transtornos de humor (42,2%) e ansiedade (16,2%), dos quais, 77,2% receberam prescrição de ansiolíticos, anticonvulsivantes ou antiepiléticos (55,5%), antidepressivos (19,2%) e estabilizador de humor (2,5%). Esses achados corroboraram o levantamento nacional realizado pela PNAUM, em que os antidepressivos e ansiolíticos estavam entre as classes farmacológicas mais utilizadas na atenção primária no Brasil 2 .…”
Section: Discussionunclassified